A Global Review of Food-Based Dietary Guidelines. Issue 4 (30th April 2019) - Herforth, Anna; Arimond, Mary; Álvarez-Sánchez, Cristina; Coates, Jennifer; Christianson, Karin; Muehlhoff, Ellen
ABSTRACT: The objective of this review is to provide a concise, descriptive global review of current food-based dietary guidelines (FBDG), and to assess similarities and differences in key elements of a healthy diet articulated across countries. Information was sourced from the FBDG repository of the FAO, which catalogs FBDG for all countries where they are available, including a description of the food guide (the graphic representation of the dietary guidelines), a set of key messages, and downloadable documents provided by the countries. FBDG are currently available for 90 countries globally: 7 in Africa, 17 in Asia and the Pacific, 33 in Europe, 27 in Latin America and the Caribbean, 4 in the Near East, and 2 in North America. The year of publication of current versions ranges from 1986 to 2017 (mean 2009). This review provides summaries of the key messages and food guides that are used to communicate national dietary guidance, organized by food group, and evaluates the extent to which each set of FBDG includes existing recommendations articulated by the WHO. Some guidance appears nearly universally across countries: to consume a variety of foods; to consume some foods in higher proportion than others; to consume fruits and vegetables, legumes, and animal-source foods; and to limit sugar, fat, and salt. Guidelines on dairy, red meat, fats and oils, and nuts are more variable. Although WHO global guidance encourages consumption of nuts, whole grains, and healthy fats, these messages are not universally echoed across countries. Future frontiers in FBDG development include the incorporation of environmental sustainability and increased attention to sociocultural factors including rapidly changing dietary trends. Steps toward regional and global dietary recommendations could be helpful for refinement of country-level FBDG, and for clear communication and measurement of diet quality both nationally and globally.